Tightened constraints on the time-lag between Antarctic temperature and CO 2 during the last deglaciation - T. D. van Ommen; S. O. Rasmussen; J. B. Pedro (Climate of the Past, 2012)
Antarctic ice cores provide clear evidence of a close coupling between variations in Antarctic temperature and the atmospheric concentration of CO 2 during the glacial/interglacial cycles of at least the past 800-thousand years. Precise information on the relative timing of the temperature and CO 2 changes can assist in refining our understanding of the physical processes involved in this coupling. Here, we focus on the last deglaciation, 19 000 to 11 000 yr before present, during which CO 2 concentrations increased by ~80 parts per million by volume and Antarctic temperature increased by ~10 °C. Utilising a recently developed proxy for regional Antarctic temperature, derived from five near-coastal ice cores and two ice core CO 2 records with high dating precision, we show that the increase in CO 2 likely lagged the increase in regional Antarctic temperature by less than 400 yr and that even a short lead of CO 2 over temperature cannot be excluded. This result, consistent for both CO 2 records, implies a faster coupling between temperature and CO 2 than previous estimates, which had permitted up to millennial-scale lags.